Acceptance Analysis of ‘X Super-App’ Digital Banking Service Through TAM and TPB Integration - Pangestika Krisnamurti; Anny Ratnawati; Agustina Widi (School of Business, IPB University (SB-IPB), 2022)
Society 5.0 has created a digital transformation phenomenon that provides new opportunities and challenges for all industries, including the banking industry. Bank X developed a digital banking service, namely X Super-App, to face the phenomenon. This research aims to examine the acceptance of X Super-App by identifying user characteristics and analyzing the influence of personal factors and social influence factors on X Super-App acceptance using the technology acceptance model and the theory of planned behavior variables. The sample in this study was 191 respondents selected by the purposive sampling technique. Data analysis used the SEM PLS method, and the descriptive method refers to questionnaires data, and literature studies. The results showed that personal and social influence factors significantly affected the acceptance of X Super-App. The proposed solutions are adding new features to the X Super-App and maintaining the stability of the X Super-App. Keywords: digital banking service, digital transformation, technology acceptance, technology acceptance model, theory of planned behavior